Manifestasi Perilaku Gaslighting sebagai Bentuk Kekerasan Psikologis: Kajian Kriminologi Visual dalam Drama The Art of Sarah - Irna Keisha Putri; Triny Srihadiati (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to analyze the manifestation of gaslighting behavior as a form of psychological violence within the South Korean mystery-thriller drama The Art of Sarah (2026). Using a qualitative descriptive approach, this study employs Charles Sanders Peirce’s semiotic triangle meaning model comprising sign, object, and interpretant to investigate how the drama visualizes systematic psychological manipulation. Data were collected through systematic observation of the series, focusing on the main character, Sarah Kim, and her manipulative interactions with other characters. The findings reveal that gaslighting in The Art of Sarah is not merely an interpersonal conflict but a structured instrument of structural aggression used to exploit social vulnerabilities and achieve status. The manipulation is executed through visual aggression, symbolic guilt tripping, and the distortion of the victim's epistemic authority. Furthermore, this study demonstrates how The Art of Sarah serves as a form of counter-visuality, exposing the ideological construction behind the perpetrator’s false narrative. The study concludes that gaslighting has evolved into a strategic methodology for social mobility, necessitating enhanced public visual literacy to recognize and prevent non-physical criminal acts.